Professional indentities, agencies and business models: notes on the history of advertising in Brazil - Aucar, Bruna (2020)
This paper analyzes the constitution of the advertising field from the birth of companies that organize productive models and professional identities around collective actions. It is based on the premise that the agency was the institution responsible for outlining the conditions for the existence of a segment, which had never existed before. This study concentrates on the examination of the first professional dispositions instituted by the agencies between the mid-nineteenth and early twentieth centuries in the United States and Europe and the subsequent reproduction of this pattern of business in Brazil. Thus, it is sought to highlight, with the historical path of these pioneer agencies, the emergence of professional functions and their forms of action combined for the social recognition of advertising field.